2018
DOI: 10.1111/ejn.14081
|View full text |Cite
|
Sign up to set email alerts
|

Contactin‐associated protein‐like 2, a protein of the neurexin family involved in several human diseases

Abstract: Contactin-associated protein-like 2 (CASPR2) is a cell adhesion protein of the neurexin family. Proteins of this family have been shown to play a role in the development of the nervous system, in synaptic functions, and in neurological diseases. Over recent years, CASPR2 function has gained an increasing interest as demonstrated by the growing number of publications. Here, we gather published data to comprehensively review CASPR2 functions within the nervous system in relation to CASPR2-related diseases in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 142 publications
0
60
0
1
Order By: Relevance
“…For example, LGI1 antibodies can disrupt interactions between LGI1 and its receptors ADAM22/23, internalise the LGI1–ADAM complex and trigger neuronal hyperexcitability and memory deficits in vivo passive transfer models. 20 21 25 42 There is also clear evidence supporting the pathogenicity of CASPR2 antibodies with rodent passive transfer reproducing human pain manifestations, and evidence that the antibodies can disrupt CASPR2 interactions with contactin-2 22 . 43…”
Section: Features Associated With Double-negative Vgkc Antibodiesmentioning
confidence: 99%
“…For example, LGI1 antibodies can disrupt interactions between LGI1 and its receptors ADAM22/23, internalise the LGI1–ADAM complex and trigger neuronal hyperexcitability and memory deficits in vivo passive transfer models. 20 21 25 42 There is also clear evidence supporting the pathogenicity of CASPR2 antibodies with rodent passive transfer reproducing human pain manifestations, and evidence that the antibodies can disrupt CASPR2 interactions with contactin-2 22 . 43…”
Section: Features Associated With Double-negative Vgkc Antibodiesmentioning
confidence: 99%
“…CASPR2 is a membrane protein expressed in the central and peripheral nervous system, particularly in the cortex, limbic system, basal ganglia, brainstem, thalamus, and sensory organs (Gordon et al, 2016). It is a cell adhesion molecule of the neurexin family responsible for synapse formation, regulation, and neuronal network establishment (Horresh et al, 2008;Saint-Martin et al, 2018).…”
Section: Anti-caspr2 Encephalitismentioning
confidence: 99%
“…Studies have shown that mutations in the gene encoding CASPR2 lead to focal epilepsy, mental retardation, schizophrenia, and other neuropsychiatric problems (Friedman et al, 2008;Saint-Martin et al, 2018;Strauss et al, 2006). Hence, comparable clinical syndrome would be justified in patients with anti-CASPR2 antibodies as well.…”
Section: Anti-caspr2 Encephalitismentioning
confidence: 99%
“…Genetic mutations that lead to functional weakness of Reelin have been shown to cause slight cortical abnormalities, including the increase in the number of neurons in the WM and abnormal brain function, in mutant mice during their adulthood . Contactin‐associated protein‐like 2 ( Cntnap2 ) encodes a neuronal transmembrane protein, a member of the neurexin superfamily, and has been shown to be associated with the risk of development of various neuropsychiatric disorders, including ASD, intellectual disability, attention deficit hyperactivity disorder, epilepsy, and schizophrenia . Cntnap2 ‐knockout mice exhibit the core behavioral deficits of ASD and altered migration of the cortical excitatory neurons .…”
Section: What Is the Cause(s) Of The Increased Densities/number Of Wmmentioning
confidence: 99%
“…58,59 Contactin-associated protein-like 2 (Cntnap2) encodes a neuronal transmembrane protein, a member of the neurexin superfamily, and has been shown to be associated with the risk of development of various neuropsychiatric disorders, including ASD, intellectual disability, attention deficit hyperactivity disorder, epilepsy, and schizophrenia. 60,61 Cntnap2-knockout mice exhibit the core behavioral deficits of ASD and altered migration of the cortical excitatory neurons. 62 Similarly, mutations in the autism susceptibility candidate 2 (AUTS2) gene have been shown to be associated with the risk of development of neurodevelopmental disorders, including ASD.…”
Section: Migration Failure Of the Neocortical Neuronsmentioning
confidence: 99%